Structural Changes in the Posterior Interosseous Nerve from Patients with Wrist Osteoarthritis and Asymptomatic Controls - Swärd, Elin; Nennesmo, Inger; Wilcke, Maria (Journal of Wrist Surgery, 2020)
Background Posttraumatic morphological changes have been described in the posterior interosseous nerve (PIN) after mild wrist trauma, and it has been suggested that posttraumatic nerve changes may contribute to wrist pain. PIN excision has shown to relieve pain in some patients with wrist osteoarthritis. However, is not known if PINs from osteoarthritic wrist have pathological features.Objective The aim of this study was to investigate whether PINs from osteoarthritic wrists show morphological changes that are not present in healthy wrists.Materials and Methods PINs resected from 15 osteoarthritic wrists were analyzed with light microscopy regarding morphological changes and compared with five asymptomatic controls without osteoarthritis.Results No significant differences in fascicular area, myelinated fiber density or myelinated fiber diameter were found. However, most patients and controls exhibited some degree of pathology, and a few samples from both groups exhibited severe pathological changes.Conclusions Our findings of morphological changes in both patients with osteoarthritis and asymptomatic controls suggest that pathological changes of unknown significance might exist in the general population in the PIN at wrist level. We believe that the observed structural nerve changes in the PIN are unlikely to contribute to the symptoms of pain. Further studies of the normal histological appearance of the terminal PIN are needed.Level of Evidence This is Level II study.
Keywords: myelinated fiber; nerve morphology; peripheral nerve; posterior interosseous nerve; wrist osteoarthritis